The Falklands War on the British Screen: Plural Memories of an Occulted War - Anne-Lise Marin-Lamellet (Revue LISA)
The representation of the Falklands War in British cinema is fragmentary, even elliptical, and focuses on the consequences and trauma of the conflict on the veterans or the relatives of those who died in combat. These films convey a critical discourse against institutions (government, army, media) while soldiers are seen as victims, embarrassing witnesses of recent events that many would rather forget. The memory of the dead is more easily honoured, but it is sometimes taken up by ideologues who confuse patriotism with exacerbated nationalism. This conflict is an opportunity for many civilians or veterans to adopt a warlike vocabulary and to see themselves as soldiers in a new kind of fight, the stake being national identity at a time when the country is perceived to be in decline. This anamnestic representation seems to show the difficulty there is in dealing with a controversial conflict from the winners’ side without appearing imperialistic, hence perhaps the choice to approach this conflict from the angle of psychological drama rather than war film. This filmography can be interpreted as a form of repentance for what is now often perceived as an upsurge of postcolonial hubris and raises the question of how to remember a war that is anything but heroic.